Maternal Embryonic Leucine Zipper Kinase Promotes Tumor Growth and Metastasis via Stimulating FOXM1 Signaling in Esophageal Squamous Cell Carcinoma - Chen, Liang; Wei, Qiuren; Bi, Shuning; Xie, Songqiang (Frontiers in Oncology, 2020)
Esophageal squamous cell carcinoma (ESCC) is a common gastrointestinal malignancy and is one of the most important cause of cancer related mortalities in the world. However, there is no clinically effective targeted therapeutic drugs for ESCC due to lack of valuable molecular therapeutic targets. In the present study, we investigated the biological function and molecular mechanisms of maternal embryonic leucine zipper kinase (MELK) in ESCC. The expression of MELK mRNA and protein was determined in cell lines and clinical samples of ESCC. MTT, focus formation and soft agar assays were carried out to measure cell proliferation and colony formation. Wound healing and transwell assays were used to assess the capacity of tumor cell migration and invasion. Nude mice models of subcutaneous tumor growth and lung metastasis were performed to examine the function of MELK in tumorigenecity and metastasis of ESCC cells. High expression of MELK was observed in ESCC cell line and human samples, especially in the metastatic tumor tissues. Moreover, overexpression of MELK promoted cell proliferation, colony formation, migration and invasion, and increased the expression and enzyme activity of MMP-2 and MMP-9 in ESCC cells. More importantly, enhanced expression of MELK greatly accelerated tumor growth and lung metastasis of ESCC cells in vivo. In contrast, knockdown of MELK by lentiviral shRNA resulted in an opposite effect both in vitro and in animal models. Mechanistically, MELK facilitated the phosphorylation of FOXM1, leading to activation of its downstream targets (PLK1, Cyclin B1 and Aurora B), and thereby promoted tumorigenesis and metastasis of ESCC cells. In conclusion, MELK enhances tumorigenesis, migration, invasion and metastasis of ESCC cells via activation of FOXM1 signaling pathway, suggesting MELK is a potential therapeutic target for ESCC patients, even those in an advanced stage.